2020
DOI: 10.2337/dc20-0961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tailored Text Messaging Intervention Among Diverse Adults With Type 2 Diabetes: Evidence From the 15-Month REACH Randomized Controlled Trial

Abstract: OBJECTIVE Text messaging interventions have high potential for scalability and for reductions in health disparities. However, more rigorous, long-term trials are needed. We examined the long-term efficacy and mechanisms of a tailored text messaging intervention. RESEARCH DESIGN AND METHODS Adults with type 2 diabetes participated in a parallel-groups, 15-month randomized controlled trial and were assigned to receive Rapid Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…The average duration of interventions, was 9 months, and the studies varied in the intensity of contact with participants from daily, weekly, to monthly—depending on the intervention modality. Telehealth interventions were primarily delivered by telephone calls [ 30 – 33 ], text messages [ 31 , 34 ], web-based portals [ 33 , 35 ], and virtual visits [ 36 ]. Patient-level only interventions primarily involved delivering diabetes self-management education (DSME) [ 30 , 31 , 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average duration of interventions, was 9 months, and the studies varied in the intensity of contact with participants from daily, weekly, to monthly—depending on the intervention modality. Telehealth interventions were primarily delivered by telephone calls [ 30 – 33 ], text messages [ 31 , 34 ], web-based portals [ 33 , 35 ], and virtual visits [ 36 ]. Patient-level only interventions primarily involved delivering diabetes self-management education (DSME) [ 30 , 31 , 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth interventions were primarily delivered by telephone calls [ 30 – 33 ], text messages [ 31 , 34 ], web-based portals [ 33 , 35 ], and virtual visits [ 36 ]. Patient-level only interventions primarily involved delivering diabetes self-management education (DSME) [ 30 , 31 , 34 36 ]. One patient-level intervention involved the use of remote monitoring devices assessing blood pressure control and blood glucose levels, pared with counseling and lifestyle recommendations specific to the patient [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although effects were small, individual incremental improvements in adherence, self‐care, or blood pressure have important implications on a population level. 64 , 65 An interactive text messaging intervention in the ED is a promising approach for identifying and engaging with otherwise difficult‐to‐reach or high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent publications of text messaging for people with diabetes, the Self-Management Support for Blood Glucose (SMS4BG) programme, the Cardiovascular Health and Text Messaging-Diabetes Mellitus (CHAT-DM) study and the Rapid Education/Encouragement and Communication for Health (REACH) programme have demonstrated small improvements in HbA1c of 0.3%-0.4% (3-4 mmol/mol). [41][42][43] There are studies showing the effectiveness of DHI interventions during pregnancy for weight management. For example, Guo et al's 44 RCT showed evidence of less weight gain among those using a mobile medical application compared with control (3.2±0.8 vs 4.8±0.7, p<0.001).…”
Section: Discussionmentioning
confidence: 99%